Rangkaian Osilator Cincin dengan Sinyal Keluaran Quadrature untuk Aplikasi Komunikasi Nirkabel - Prapto Nugroho (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2012)
This paper proposes a novel voltage controlled ring oscillator with quadrature output in 0.18 m CMOS technology. Interpolating inverter and sub-feedback loop is used to reduce the power consumption and increase the output frequency. It consumes only 3.3 mA from 1.8V supply voltage to oscillate at 4.4 GHz. It has wide tuning range from 0.6 GHz to 5 GHz or about 152% from center frequency. Phase noise of -103.1 dBc/Hz is achieved at 4.4 GHz carrier and 4 MHz frequency offset. Figure of Merit (FoM) is -156.1 dBc/Hz which is the best among its previous published reference papers.